2016
DOI: 10.1021/acs.jmedchem.6b01450
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small Molecules with a Noncanonical Binding Mode to HIV-1 Trans Activation Response (TAR) RNA

Abstract: Small molecules that bind to RNA potently and specifically are relatively rare. The study of molecules that bind to the HIV-1 transactivation response (TAR) hairpin, a cis-acting HIV genomic element, has long been an important model system for the chemistry of targeting RNA. Here we report the synthesis, biochemical and structural evaluation of a series of molecules that bind to HIV-1 TAR RNA. A promising analog, 15, retained the TAR binding affinity of the initial hit and displaced a Tat-derived peptide with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…We focused our assays on peptide mimics because the structure of free pre-miR21 revealed a highly flexible large apical loop that presents a very challenging target for small molecule chemistry. Outside of the larger apical loop, the pre-mIR21 hairpin appears devoid of unique structural features that would provide binding site for small molecules, as observed for example in other RNAs targeted for drug discovery such as TAR or RRE from HIV, or the Hep C IRES 9, 24, 63 . The relaxed structure of the hairpin suggested to us that ligands with larger interface area, such as peptides, would be required to gain the binding energy required to conformationally constrain the apical loop and compensate the entropic loss associated with loop rigidification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused our assays on peptide mimics because the structure of free pre-miR21 revealed a highly flexible large apical loop that presents a very challenging target for small molecule chemistry. Outside of the larger apical loop, the pre-mIR21 hairpin appears devoid of unique structural features that would provide binding site for small molecules, as observed for example in other RNAs targeted for drug discovery such as TAR or RRE from HIV, or the Hep C IRES 9, 24, 63 . The relaxed structure of the hairpin suggested to us that ligands with larger interface area, such as peptides, would be required to gain the binding energy required to conformationally constrain the apical loop and compensate the entropic loss associated with loop rigidification.…”
Section: Resultsmentioning
confidence: 99%
“…However, riboswitches and aptamers represent uniquely complex structured RNAs, which were naturally or artificially selected to bind to small molecules 1214 . Developing small molecules to specifically target RNA structures typically involved in protein-RNA interactions that subtend ncRNA function (stem loops, internal loops, and bulges) remains extremely challenging, despite significant efforts over the last two decades 8, 9, 1521 .…”
mentioning
confidence: 99%
“…During the past 2 decades, multiple labs have worked to identify small molecules that bind HIV-1 TAR (64,(85)(86)(87)(88)(89)(90)(91). To gain perspective about the successes and ongoing challenges, it is instructive to examine the handful of structurally characterized TAR-small molecule complexes to assess compound localization and commonalities in their modes of molecular recognition.…”
Section: Targeting Tar With Small Moleculesmentioning
confidence: 99%
“…8-10 It is worth noting, however, that aminoglycosides and their multivalent analogs have featured prominently in several studies elucidating high affinity interactions with RNA and have demonstrated utility in studying RNA biology. 23-30 Although significant advances have recently been made towards rationally designing small molecule ligands for RNA, 9,14,31-37 the limited available knowledge of the guiding principles of small molecule:RNA recognition has remained a significant hurdle. At the same time, some of the most successful screens have been conducted on RNA-targeted libraries generated by the diversification of molecular scaffolds known to interact with RNA, such as phenylbenzamidazoles, 38-40 oxazolidinones, 41-44 and diphenylfurans 45-47 though the library sizes and number of scaffolds tested has been fairly limited.…”
Section: Introductionmentioning
confidence: 99%